THE RELATIONSHIP BETWEEN DIAGNOSIS AND SEVERITY OF ISCHEMIC STROKE AND SERUM UROTENSIN-II LEVELS - Aytac, Emrah; Akpinar, Cetin Kursad (Carbone Editore, 2018)
Introduction: Introduction: Urotensin-II is an extremely potent, widespread vasopressor and increased serum urotensin-II level is associated to many disorders including congestive heart failure, hypertension, coronary artery diseases, diabetes mellitus and metabolic syndromes. In this study we aimed to investigate whether there is a relationship between serum urotensin-II level and etiology and severity of stroke in patients with ischemic cerebrovascular disease. Materials and methods: The study included 20 patients experienced acute ischemic cerebrovascular event (study group) and 20 healthy individuals (control group). Venous blood samples were drawn from patients who experienced acute ischemic stroke within prior 12 hours and urotensin-II measurements were performed by ELISA kits using sandwich enzyme-linked sorbent immunoassay method. Results: No significant difference was observed in serum urotensin-II levels between study and control groups. In the analysis of ischemic stroke subgroups, urotensin-II level was found to be significantly higher in patients with cardioembolic stroke. In addition, a positive correlation was detected between urotensin-II level and high National Institutes of Health Stroke Scale (NIHSS) score at presentation. Conclusion: This is the first study analysing urotensin-II levels in stroke, concluding that urotensin-II could be a relevant parameter for assessment of etiology and severity of stroke.
Keywords: urotensin-II; ischemic stroke; severity; cardioembolic stroke